2020
DOI: 10.1017/ice.2020.236
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating preauthorization into antimicrobial stewardship pharmacist workflow reduces Clostridioides difficile and gastrointestinal panel testing

Abstract: Objective: To evaluate whether incorporating mandatory prior authorization for Clostridioides difficile testing into antimicrobial stewardship pharmacist workflow could reduce testing in patients with alternative etiologies for diarrhea. Design: Single center, quasi-experimental before-and-after study. Setting: Tertiary-care, academic medical center in Ann Arbor, Michigan. Patients: Adult and pediatric patients admitted between September 11, 2019 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The bias generated by the under-reported data impacts our model’s parameter estimation, since the diagnosis capacity, compared to the number of cases in the population, changes over time. Recent works have demonstrated and have argued that the delay into case reports and the mitigation strategies may directly impact the estimation 27 , 28 . With more information about the available data and complex models, fitting the model parameters to the epidemic curve would be an interesting approach worthy of study.…”
Section: Discussionmentioning
confidence: 99%
“…The bias generated by the under-reported data impacts our model’s parameter estimation, since the diagnosis capacity, compared to the number of cases in the population, changes over time. Recent works have demonstrated and have argued that the delay into case reports and the mitigation strategies may directly impact the estimation 27 , 28 . With more information about the available data and complex models, fitting the model parameters to the epidemic curve would be an interesting approach worthy of study.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have used similar models to improve diagnostic stewardship of C. difficile . Two studies of antimicrobial stewardship pharmacist approval of C. difficile orders showed a significant decrease in orders 7 and a significant reduction in C. difficile HAIs after implementation. 13 In 2 studies that utilized infection prevention approval of orders, decreases occurred in testing and C. difficile HAIs.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, various studies have shown that administrative or laboratory test restriction for C. difficile, rather than passive decision support more effectively improve diagnostic stewardship of C. difficile. 1,[6][7][8] Passive decision support via alerts can result in "alert fatigue," in which providers no longer engage with the alert due to overfiring. 5 Root-cause analyses performed prior to the intervention identified diagnostic stewardship as an opportunity for hospitals A and B. Unadjusted baseline C. difficile HAI rates for hospital A were 8.83 and 8.36 per 10,000 patient days in 2020 and 2021 and for hospital B these rates were 7.03 and 9.34 per 10,000 patient days in 2020 and 2021.…”
mentioning
confidence: 99%
“…Approximately 4%–15% of hospitalized patients and 50% of long-term care patients are asymptomatically colonized with C. difficile . 1 , 2 , 7 Without 2-step testing to detect toxin production, NAAT must be ordered properly to avoid overdiagnosis of CDI in general. Inconsistent definition and documentation of diarrhea, laxative use dismissal, leukocytosis, and perception of “increased-risk” for CDI are factors that drive inappropriate C. difficile testing.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent definition and documentation of diarrhea, laxative use dismissal, leukocytosis, and perception of “increased-risk” for CDI are factors that drive inappropriate C. difficile testing. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%